Kajian Etis dalam Cerpen-Cerpen Koran Digital Jawapos.com Periode Maret 2020-Desember 2021 - Habib P, Muhammad; Mujtaba, Sahlan; Hartati, Dian (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research focuses on human etiquette issues towards the environment. All forms of damage and changes to the environment are depicted through news stories and digital newspaper short stories. Ethical studies are raised to examine the attitudes that humans should have towards the environment to create harmony. Through environmentally themed digital newspaper short stories, the researcher explains the forms of environmental damage and changes and their relation to how human characters respond to them. The method used is qualitative to comprehensively and deeply understand the phenomenon under study. The results of the ethical study of five digital newspaper short stories as research objects. The analysis shows that the ethical analysis of environmental wisdom describes: an examination of attitudes towards the environment, namely an examination of respect for nature; an examination of moral responsibility towards nature; an examination of solidarity towards nature; an examination of love for nature; and an examination of not disturbing natural life. The analysis results show findings of ethical study of environmental wisdom in terms of attitude studies found in digital newspaper short stories. Three of them have a comprehensive study of attitudes towards the environment, while the other two only have one individual attitude study towards the environment